2023
DOI: 10.1136/bmj-2022-074325
|View full text |Cite
|
Sign up to set email alerts
|

Comparative effectiveness of heterologous third dose vaccine schedules against severe covid-19 during omicron predominance in Nordic countries: population based cohort analyses

Abstract: Objective To investigate the comparative vaccine effectiveness of heterologous booster schedules (ie, three vaccine doses) compared with primary schedules (two vaccine doses) and with homologous mRNA vaccine booster schedules (three vaccine doses) during a period of omicron predominance. Design Population based cohort analyses. Setting Denmark, Finland, Norway, and Sweden, 27 December 2020 to 31 December 202… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
6
0

Year Published

2023
2023
2025
2025

Publication Types

Select...
9
1

Relationship

1
9

Authors

Journals

citations
Cited by 15 publications
(7 citation statements)
references
References 39 publications
1
6
0
Order By: Relevance
“…While several studies reported a higher effectiveness of mRNA-1273 compared to BNT162b2 against infection and severe COVID-19 outcomes both as a primary and booster vaccination [ 51 , 52 , 53 , 54 , 55 , 56 ], in the present cohort we observed a significantly higher protection of mRNA-1273 only against SARS-CoV-2 infections or after a single dose, and the subjects who received three or more doses of mRNA-1273 showed a higher likelihood of death, as compared to the recipients of BNT162b2 only. In contrast, we observed a greater protection conferred by heterologous booster (mixed) vaccination compared with a homologous booster with BNT162b2 only, in line with the findings of immunogenicity [ 57 ] and other population-based [ 20 , 58 , 59 ] studies. Notably, however, the results are difficult to compare due to the diverse booster schedules adopted across countries.…”
Section: Discussionsupporting
confidence: 90%
“…While several studies reported a higher effectiveness of mRNA-1273 compared to BNT162b2 against infection and severe COVID-19 outcomes both as a primary and booster vaccination [ 51 , 52 , 53 , 54 , 55 , 56 ], in the present cohort we observed a significantly higher protection of mRNA-1273 only against SARS-CoV-2 infections or after a single dose, and the subjects who received three or more doses of mRNA-1273 showed a higher likelihood of death, as compared to the recipients of BNT162b2 only. In contrast, we observed a greater protection conferred by heterologous booster (mixed) vaccination compared with a homologous booster with BNT162b2 only, in line with the findings of immunogenicity [ 57 ] and other population-based [ 20 , 58 , 59 ] studies. Notably, however, the results are difficult to compare due to the diverse booster schedules adopted across countries.…”
Section: Discussionsupporting
confidence: 90%
“…In this study, 87.8% of heterologous vaccination series included an mRNA booster dose. According to a previous comparative analysis, heterologous booster schedules conferred slightly better protection against COVID-19-related outcomes than homologous mRNA vaccine booster schedules [29].…”
Section: Discussionmentioning
confidence: 97%
“…The reasons for the high attack rate during the study period are complicated, but the main reason should be it has been a long time (about 8–12 months) since the last dose of vaccination. The durability of the protection of COVID-19 vaccines is not good and the protection waned quickly after the vaccination, regardless of the types of COVID-19 vaccines, which has been wildly observed [ 19 ]. In addition, another probable reason is that the population in China had taken a zero-COVID policy and experienced a long period of lock-down with no natural exposure to any SARS-CoV-2 virus, which hurdled to achieve herd immunity against COVID-19, while the SARS-CoV-2 were spreading around in other areas.…”
Section: Discussionmentioning
confidence: 99%